The Factors Analysis that Influence the Employment Absorption at Songket Industry in Palembang-South Sumatra Province, Indonesia - M. Yusuf, (Journal of Human Development and Communication (JoHDeC), 2025)
The population growth in the country of Indonesia is getting old is not diminishing but is growing. Palembang is one of metropolitan city in Indonesia. The number of people unemployed in this city is quite a number. Unemployment is generally caused because the labor force is not proportional to the number of jobs that can absorb them. Many companies in Palembang are also benchmarks of employment absorption and reduce the unemployment number of processing industry into sectors are relied for the expansion of job creation. Especially, in the branches of labor-intensive industries. The problem of the industry certainly is not only directed to the large and medium industries, but the attention that commensurate must also be directed at small industries and households that many found in the countryside. The small industries and households have played an important role in the national economy. This research aimed to analyze the factors that affecting employment absorption in the songket industry in Palembang. There are four variables that affecting employment absorption in the convection industry, i.e., capital, sales volume, level of education, and level of wage. Data analysis technique is used in this research is multiple regression analysis. This analysis technique is used to determine how far influence the capital, volume of sales, the level of education and the level of wage on employment absorption. These results indicate that the variable of education level has a very high impact on employment absorption. For variable of sales volume and wage levels have a high impact on employment absorption.